Knowledge Management As A Strategic Tool In Crisis Management And Decision-Making - Abdulrezag Farag Benhalim (Journal of Scientific and Human Dimensions, 2025)
The research aims to identify the role of knowledge management as a strategic tool in enhancing crisis management and supporting the decision-making process within institutions. The research problem is represented in the weakness of this role. The researcher employed the descriptive methodology in this study. In the applied framework, the research sample included department directors, office managers, heads of divisions, and several employees in the Crisis Management Department at the National Center for Emergency, Crisis, and Disaster Management. The sample consisted of 28 individuals out of a total of 136 employees at the Center, representing 20.5% of the total workforce. The questionnaire was divided into four main dimensions: knowledge management, crisis management, decision-making, and the relationship between knowledge management, crisis management, and decision-making. Based on the statistical analysis of the respondents’ answers to the questionnaire, and through testing the research hypotheses, the analysis indicated several key findings. The Center regularly collects knowledge and information relevant to its operations at a rate of 100%. However, tacit knowledge (employees’ experience and skills) is neither documented nor shared among staff, as confirmed by 92.8% of participants who selected “disagree.” Similarly, 92.8% of respondents confirmed that the Center does not have clear and written plans for dealing with potential crises. On the other hand, 92.4% of participants affirmed the existence of periodic training for employees on crisis scenarios. Additionally, 89.3% confirmed that decisions made within the Center are based on accurate and reliable information. Accordingly, the research findings indicate that the level of knowledge management within institutions is a fundamental factor for the success of crisis management and the improvement of decision-making quality. Among the most important recommendations of the study are the necessity of documenting tacit knowledge (employees’ experience and skills) and sharing it among staff; the need for clear and written plans to manage potential crises; and ensuring that decisions made during crises are effective and well-informed.